Analysis and Design of Food Price Data Processing Information System - Priska, Salsa Dilah; Syahrullah, Syahrullah; Nugraha, Deny Wiria; Lapatta, Nouval Trezandy; Lamasitudju, Chairunnisa Ar (Universitas Raharja, 2026)
Food prices have an important role in maintaining economic stability and public welfare, as price fluctuations can have a direct impact on purchasing power and inflation. The manual process of recording and reporting food price data at the Department of Agriculture and Food Security of Palu City leads to inefficiencies, data inaccuracies, and difficulties in tracking historical information. These limitations highlight the need for a structured system that can support accurate and efficient data management. This study applies a prototyping method to develop a web-based information system tailored to the needs of the institution. The development process involves continuous interaction between users and developers to ensure the system meets practical requirements. Data were collected through interviews, observations, and documentation. System functionality was tested using black box testing, while usability was assessed using the System Usability Scale (SUS) questionnaire. The results indicate that the system's features, including daily price input, automatic average calculations, report submission, and approval workflows, function correctly. Users are able to interact with the system efficiently, and the SUS results show that the system falls into the acceptable usability category, indicating that it is easy to use. In conclusion, the development of this web-based information system improves the efficiency and accuracy of food price data processing and reporting. It provides a reliable tool for managing information within the department and supports better operational performance.